2005
DOI: 10.1021/nl050155a
|View full text |Cite
|
Sign up to set email alerts
|

Periodic DNA Nanotemplates Synthesized by Rolling Circle Amplification

Abstract: Rolling circle amplification (RCA) is an elegant biochemical method by which long single-stranded DNA molecules with a repeating sequence motif can be readily synthesized. In RCA, small circular single-stranded oligonucleotides serve as templates for the polymerization of the complementary strand. A DNA polymerase with an efficient strand displacement activity can copy the circular template without stopping. This results in a long DNA strand with periodic sequence. We here demonstrate that this method, using D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(109 citation statements)
references
References 41 publications
3
103
0
3
Order By: Relevance
“…Due to the partially complementary sequences of these two DNA strands, they were hybridized to form a circular shape. After hybridization, the nick was enzymatically closed by T4 DNA ligase 35,36 .…”
Section: Rna Membrane Fabricationmentioning
confidence: 99%
“…Due to the partially complementary sequences of these two DNA strands, they were hybridized to form a circular shape. After hybridization, the nick was enzymatically closed by T4 DNA ligase 35,36 .…”
Section: Rna Membrane Fabricationmentioning
confidence: 99%
“…RCA is an enzymatic method that allows the fabrication of long, ss DNA of periodic sequence from cyclic templates. The resulting RCA products were employed to construct long tracks of proteins [89] and nanoparticles [90]. For the assembly of nanotubes, a circular ss DNA was combined with a primer strand and DNA polymerase Phi29 producing the periodic ss DNA Guide (Fig.…”
Section: Dna Origamimentioning
confidence: 99%
“…30 Similarly, Simmel et al obtained linear chains of NPs on longer scaffolds. 31 Kiehl et al has demonstrated the use of self-assembled 2D DNA lattices to organize AuNPs into periodic striped patterns (Fig. 11a).…”
Section: This Journal Is C the Royal Society Of Chemistry 2008mentioning
confidence: 99%